Respuesta :

Answer: The solution of the system of equations is [tex]x=\frac{-53}{11}[/tex], [tex]y=\frac{47}{11}[/tex] and [tex]z=\frac{-38}{11}[/tex].

Explanation:

The given equations are,

[tex]x+y+z=-4[/tex]            ..... (1)

[tex]-x+2y+3z=3[/tex]         ..... (2)

[tex]x-4y-2z=-15[/tex]        ...... (3)

From equation we get,

[tex]x=-4-y-z[/tex]

Put this value in equation (4) and (5).

[tex]-(-4-y-z)+2y+3z=3[/tex]

[tex]3y+4z=-1[/tex]     .... (4)

[tex](-4-y-z)-4y-2z=-15[/tex]

[tex]-5y-3z=-11[/tex]  .....(5)

Use elimination method to solve the equations (4) and (5).

Multiply equation (4) by 3 and equation (5) by 4, then add both equations as shown in figure,

[tex]-11y=-47[/tex]

[tex]y=\frac{47}{11}[/tex]

Put this value in equation (4).

[tex]3(\frac{47}{11})+4z=-1[/tex]

[tex]4z=-1-\frac{141}{11}[/tex]

[tex]4z=\frac{-11-141}{11}[/tex]

[tex]z=\frac{-152}{11\times 4}[/tex]

[tex]z=\frac{-38}{11}[/tex]

Put [tex]y=\frac{47}{11}[/tex] and [tex]z=\frac{-38}{11}[/tex] in equation (1).

[tex]x+\frac{47}{11}+\frac{-38}{11}=-4[/tex]

[tex]x+\frac{9}{11}=-4[/tex]

[tex]x=\frac{-44-9}{11}[/tex]

[tex]x=\frac{-53}{11}[/tex]

Therefore, the The solution of the system of equations is [tex]x=\frac{-53}{11}[/tex], [tex]y=\frac{47}{11}[/tex] and [tex]z=\frac{-38}{11}[/tex].

Ver imagen DelcieRiveria

Answer:

The given equations are

x + y + z = -4


-x + 2 y + 3 z = 3


x - 4 y - 2 z = -15

Writing in matrix form

A=   1     1      1             X=   x       B=   -4

     -1     2     3                    y               3            ⇒A,X,B are in matrix form.

       1     -4    -2                   z              -15

i.e  Ax=B

x =[tex]A^{-1}[/tex]B

but ,[tex]A^{-1}[/tex]=Adj.(A)/Determinant A

Determinant of A= 1(-4+12) -1(2-3)+1(4-2)=8+1+2=11

To find Adjoint of matrix A, we will find the cofactor of A and then it's transpose.

[tex]a_{11}[/tex]=-4+12=8, [tex]a_{12}=-[2-3]=1,[/tex]

[tex],a_{13}=4-2=2,\\,a_{21}=-[-2+4]=-2\\,a_{22}=-2-1=-3,\\a_{23}=-[-4-1]=5,\\a_{31}=[3-2]=1\\,a_{32}=-[3+1]=-4\\,a_{33}=2+1=3[/tex]

Now taking cofactor, and getting the adjoint

Adjoint (A)= 8     -2       1

                     1      - 3       -4

                     2       5         3

Adjoint(A). B=  -53

                        47

                         -38


[tex]\frac{Adjoint (A)\times B}{Determinant A}[/tex] =   -53/11

                                                                                        47/11

                                                                                         -38/11

So, solution set is , x=-53/11, y=47/11, z=-38/11